Photoisomerization of ionic liquid ammonium cinnamates: One-pot synthesis-isolation of Z-cinnamic acids - Salum, Maria Laura (2010)
Photoisomerization presents the only direct method for contra-thermodynamic E-Z isomerization of olefins. Synthetic applications of this method have been limited by its reversible nature, which leads to a photostationary-state mixture of both isomers. For the first time, a highly efficient one-pot preparation-isolation of solid ionic liquid Z-cinnamic acids by photoisomerization in acetonitrile solution of ionic liquid E-cinnamic acids is described.